Ofelia jaliscana, a new ennomine (Lepidoptera: Geometridae) genus and species from Mexico - Garzón-Orduña, Ivonne J. (Zootaxa, 2025)
Ofelia jaliscana Garzón-Orduña gen. nov. et sp. nov. from Chamela (Jalisco, Mexico) is described and illustrated. Morphological characters support the hypothesis that the genus belongs in the tribe Boarmiini, but no close relatives are evident due to its distinctive morphology. The diagnosis for the genus and species are provided as well as images of the male and female genitalia.